INSTRUMENTATION OF SPLIT HOPKINSON PRESSURE BAR FOR TESTING OF CELLULAR METALLIC MATERIALS - Jan Falta; Petr Zlámal; Marcel Adorna (Acta Polytechnica CTU Proceedings)
This paper presents an overview of the custom design instrumentation of a Split Hopkinson Pressure Bar modified for dynamic testing of materials with low mechanical impedance, particularly for cellular metallic materials (e. g. metal foams, laser sintered structures). Design and implementation of the components related to the strain wave measurement based on strain gauges (i.e. strain-gauge measurement unit, power supply unit, filtration) and the components used for the control and synchronization of the experiment, such as module of laser trough-beam photoelectric sensor are summarized in the paper. Aside from the design of the hardware components, the contribution deals also with development of a control software with graphical user interference using LabView (National Instruments, USA) programming environment, that allows selection of parameters of the dynamic tests and their storage for the evaluation of experiments.